Two New Energy-Preserving Algorithms for Generalized Fifth-Order KdV Equation (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, based on the multi-symplectic formulations of the generalizedfifth-order KdV equation and the averaged vector field method, two new energy-preservingmethods are proposed, including a new local energy-preserving algorithmwhich is independent of the boundary conditions and a new global energy-preservingmethod. We prove that the proposed methods preserve the energy conservation lawsexactly. Numerical experiments are carried out, which demonstrate that the numericalmethods proposed in the paper preserve energy well.